Drought in Arid and Semi-Arid Regions 2013
DOI: 10.1007/978-94-007-6636-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Associations Coping with Drought: The Case of Four Irrigation Districts in Eastern Spain

Abstract: The aim of this article is to analyze the strategies developed by water users' associations in Spain to overcome drought in a context of structural scarcity due to geographical conditions and from the development of expansionary irrigation policies. This analysis is based on interviews with farmers and representatives of water user's associations in four selected irrigation districts placed in the Valencia Region. The work demonstrates that in a relatively small area of the Mediterranean there are very differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…The evidence of the empirical and theoretical literature review suggest that when traditional surface (furrow) systems are replaced by sprinkler and drip irrigation, water abstraction (use) is reduced in a significant number of studies, among others in: Jackson et al 2010;López-Gunn et al 2012;García-Mollá et al 2013;Soto-García et al 2013;Graveline et al 2013;Heumesser et al 2012;Törnqvist and Jarsjö 2012;Peterson and Ding 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence of the empirical and theoretical literature review suggest that when traditional surface (furrow) systems are replaced by sprinkler and drip irrigation, water abstraction (use) is reduced in a significant number of studies, among others in: Jackson et al 2010;López-Gunn et al 2012;García-Mollá et al 2013;Soto-García et al 2013;Graveline et al 2013;Heumesser et al 2012;Törnqvist and Jarsjö 2012;Peterson and Ding 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other empirical analyses of the transformation of irrigated systems in Spain with the abovementioned land constraints have been conducted by Soto-García et al (2013), Fernández-García et al (2014 and García-Mollá et al (2013). All the authors concluded that water diversion (abstraction) was significantly reduced (by 25%-45%), but that water depletion (evapotranspiration) did not increase.…”
Section: Empirical Researchmentioning
confidence: 99%
“…For instance, the water available to the ARJ district has been reduced from 700 to 200 M m 3 in the last 40 years. Consequently, the dwindling return flows from the irrigation districts have caused serious environmental problems to the Albufera wetland, the main aquatic ecosystem in the JRB, which is mostly fed by these return flows (García-Molla et al, 2013).…”
Section: The Jucar River Basin: Background Informationmentioning
confidence: 99%
“…Hence, the impact of policies on irrigation modernization is uncertain; particularly the degree to which the introduction of new technologies might help to reduce rates of water use and consumption [8]. Although changing irrigation systems, from furrow to micro-irrigation (i.e., drip method), has reduced water use in some cases [9,10], other studies suggest it has been associated with increased water and energy consumption [11,12].…”
Section: Introduction: Groundwater Management Crisis In Iranmentioning
confidence: 99%